2021
DOI: 10.5455/javar.2021.h550
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, species composition, and associated risk factors of small ruminant gastrointestinal nematodes in South Omo zone, South-western Ethiopia

Abstract: Objective: This study was conducted to generate data on the prevalence, species composition, and factors associated with small ruminant nematode infection in the South Omo zone, in South-western Ethiopia. Material and Methods: A cross-sectional study through fecal nematode parasite examination was conducted. Simple floatation test and coproculture, followed by Baermann technique, were used for nematode egg and third-stage larvae (L3) separation and identification. The M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…This finding was very closer to the reports from various parts of Ethiopia [25]. A higher prevalence than the current study was reported from various parts of the country [16,[26][27][28][29] that could be due to differences in climatic and environmental factors and management factors [30]. The univariable and multivariable logistic regression analyses revealed that flock size, age and sex of goats, and season were significantly (p < 0 05) influencing the infection of goats by gastrointestinal nematodes.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding was very closer to the reports from various parts of Ethiopia [25]. A higher prevalence than the current study was reported from various parts of the country [16,[26][27][28][29] that could be due to differences in climatic and environmental factors and management factors [30]. The univariable and multivariable logistic regression analyses revealed that flock size, age and sex of goats, and season were significantly (p < 0 05) influencing the infection of goats by gastrointestinal nematodes.…”
Section: Discussionsupporting
confidence: 82%
“…Faecal egg count reduction for anthelmintic resistance test in goats.These nematode genera are commonly circulating in Gamo and Gofa zones and the surrounding areas[16,28,44,45] and other parts of the country[4,28,[46][47][48][49][50][51]. According to Bishop and Morris[52], these parasites, mainly Haemonchus spp., Trichostrongylus spp., and Teladorsagia spp., are the most common nematodes known to affect sheep and goats in sub-Saharan Africa.…”
mentioning
confidence: 99%
“…Moreover, along with helminth eggs, it’s consistent with finding of different study areas across Ethiopia. 6 , 19 , 20 , 43 However, despite the level of incidence of the helminth infection, the strongyle-type nematode genera are more dominant parasites as described by Tibebu et al, Welay et al, Ayana et al, Tesfaye and Tongshoob et al 23 , 24 , 42 , 44 , 45 The study showed that 68.55 and 55.21% of cattle and sheep, respectively, are infested with helminthes, which is consistent with finding of Zeryehun 46 conducted to assess helminthosis of sheep and goats in and around Haramaya, Southeastern Ethiopia.…”
Section: Discussionmentioning
confidence: 98%
“…Gastrointestinal nematodes mostly infest small ruminants. Their epidemiological patterns rely on the factors related to the parasite-host (such as inadequate host nutrition, poor hygiene, and sanitation; Tesfaye et al, 2021). Among these GIT parasites, the most common parasites infesting the livestock are Hemonchus contortus, Ascaris, Strongyloids, Trichostrongyliods, Ostertagia, Trichuris, Dictyocaulus, Trichnellia, Enterobius, Cooperia, Gunagylonema, Chabertia, Oesphagostomum (Mekonen, 2021).…”
Section: Introductionmentioning
confidence: 99%